2009
DOI: 10.2319/081908-437.1
|View full text |Cite
|
Sign up to set email alerts
|

Upper Incisor Position and Bony Support in Untreated Patients as Seen on CBCT

Abstract: Objective: To test the null hypothesis that there are no correlations between the morphology of the upper jaw, the position of the upper incisors, and facial type. Materials and Methods: From a sample of 191 patients, the FMA angle was used to select 20 short face type, 20 norm face type, and 20 long face type patients, aged 12 to 40 years. Using cone-beam computed tomography (CBCT), tomography was carried out on sagittal sections corresponding to the four upper incisors. Some parameters defining the dentoskel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 14 publications
6
54
1
17
Order By: Relevance
“…This might play a role, since existing data indicate that considerable variation exists in the alveolar thickness buccal and lingual of the upper incisors according to tooth type and facial type (26). In the present study both bracket prescription and especially bracket positioning had a considerable effect on the displacement of the root apex and the crown tip ( Figure 7) and therefore might possibly affect the displacement of the root's apex.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This might play a role, since existing data indicate that considerable variation exists in the alveolar thickness buccal and lingual of the upper incisors according to tooth type and facial type (26). In the present study both bracket prescription and especially bracket positioning had a considerable effect on the displacement of the root apex and the crown tip ( Figure 7) and therefore might possibly affect the displacement of the root's apex.…”
Section: Discussionmentioning
confidence: 65%
“…Several authors have reported that a considerable variation exists in CRA, which can take values between 156° and 195° (23)(24)(25). The CRA may limit the degree to which the roots can be torqued palatally due to an increased proximity to the cortical plate of the alveolar process (22,26). Taking into consideration that a root, moved against the cortical plate, is at higher risk for root resorption (27)(28)(29), care should be taken to torque a tooth with a large CRA (20).…”
Section: Introductionmentioning
confidence: 99%
“…In orthodontics, CBCT imaging has been applied to impacted teeth, 6 assessment of bone volume, 7 cleft patients, 8 and root resorption. [9][10][11][12] But the data are still scarce even now, with regard to its application in detecting EARR.…”
Section: Introductionmentioning
confidence: 99%
“…Este tratamento tem apresentado bons resultados periodontais a longo prazo (NORDQUIST, MCNEILL, 1975;SILVA FILHO et al, 2000), quando o canino adjacente é mesializado para a região de incisivo lateral, tomando os devidos cuidados durante a reanatomização para torná-lo o mais parecido possível com um incisivo lateral. Enquanto um dente é ortodonticamente movimentado pelo alvéolo, ocorre uma remodelação óssea em volta da raiz, (ZACHRISSON, 2003) GARIB et al, 2006;GRACCO et al, 2009;NAUERT, BERG, 1999;RUNGCHARASSAENG et al, 2007;SARIKAYA et al, 2002;VASCONCELOS et al, 2012;YATABE, 2010) KING, 1990;DORFMAN, 1978;GARIB et al, 2006;GEIGER, WASSERMAN, 1980;HOLLENDER, RONNERMAN, THILANDER, 1980;PERSSON, LENNARTSSON, 1986;SHARPE et al, 1987;SJOLIEN, ZACHRISSON, 1973;THILANDER, 1992;YAGCI et al, 2012;ZACHRISSON, ALNAES, 1973, 1974 Quando uma pressão é aplicada ao dente, leva a uma alteração no fluxo sanguíneo do ligamento periodontal, que diminui onde o ligamento é comprimido e é mantido ou aumentado onde o ligamento está sob tensão. As alterações químicas, agindo diretamente ou por estímulo da liberação de outros agentes ativos biologicamente, estimulam a diferenciação e a atividade celular.…”
Section: Lista De Figurasunclassified
“…6.1) Alguns trabalhos utilizaram cortes axiais relacionados à JCE (JANUARIO et al, 2011;YATABE, 2010), e outros utilizaram a ponta de cúspide individual de cada dente . (GRACCO et al, 2009) Em seguida, a partir de uma imagem axial na altura da junção cementoesmalte dos dentes anteriores, foram realizados cortes individuais no sentido mésio-distal a fim de se obter cortes parassagitais de cada um dos dentes a ser avaliado. (GARIB et al, 2010a;GARIB et al, 2006;GARIB et al, 2010b;GARIB et al, 2012;GARIB et al, 2010c;LOUBELE et al, 2008;MOL, BALASUNDARAM, 2008;SUN et al, 2011;YATABE, 2010) Os caninos do lado da fissura apresentaram um valor médio de 0,20mm para a ETOV e 1,39mm para a ETOL, enquanto que os caninos do lado sem fissura apresentaram 0,45mm para a ETOV e 1,44mm para a ETOL.…”
Section: A Amostraunclassified